The origins of proslavery Christianity : white and black evangelicals in colonial and antebellum Virginia - Irons, Charles F. (Charles Frederick) (Slavery in America and the world: history, culture & law., 2008)
Even though black and white evangelicals often worshipped together, white evangelicals emerged as defenders of race-based slavery. Focusing on Virginia, this book argues that white evangelical ideas about slavery grew directly out of their interactions with black evangelicals.